Effect of Heater Size on Confined Subcooled Jet Impingement Boiling - Abishek, S.; Narayanaswamy, Ramesh; Narayanan, V. (ASME, 2012)
Jet impingement boiling heat transfer is a potential technique for the removal of very high heat fluxes concentrated at discrete locations, such as in power electronic components. In the present research, the effect of heater-nozzle size ratio (in the range 0.5 ≤ wH/wN ≤ 11) on jet impingement boiling is studied numerically. A steady-state submerged and confined subcooled jet impingement boiling of de-ionized and degassed water (at atmospheric pressure) on a polished isothermal heater surface is considered for a jet Reynolds number of Rew = 2500 and 20oC subcooling. The RPI wall boiling closure is used for the partition of heat flux on the surface into liquid phase, evaporation and quenching. Turbulence is modeled using the RNG-k-ɛ mixture model. The flow and heat transfer is simulated by considering the liquid and vapor phase to be an Euler-Euler interpenetrating continua; the interfacial momentum transfer is modelled using appropriate correlations for interphase momentum, heat and mass transfers. Validation of the numerical approach was performed by comparison of the present results with experimental data from literature for axisymmetric as well as slot jets. It was found that for any prescribed wall superheat, the heat flux was consistently larger for relatively smaller heaters (or smaller wH/wN). However, for any given wall superheat, the heat flux stagnated at an apparent asymptotic limit with increase in heater size, and this asymptotic limit was larger for larger wall superheats. It was also found that the quenching heat flux was the largest contributor to the total heat flux at relatively large degrees of superheat irrespective of heater-nozzle size ratio. A correlation is also developed for the heat flux as a function of the heater size and degree of superheat, for a given set of other controlling parameters.